2008
DOI: 10.1007/s00299-008-0644-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of an R2R3-MYB transcription factor gene AtMYB118 in embryogenesis in Arabidopsis

Abstract: MYB transcription factors play important roles in various developmental processes in plants. Here we report the characterization of AtMYB118, a gene encoding a putative R2R3-type MYB transcription factor, which expresses predominantly in siliques. Real-time quantitative PCR analysis and in situ hybridization showed that the transcripts of AtMYB118 were mainly detected in developing embryos. Constitutive over-expression of AtMYB118 resulted in pleiotropic phenotypes, including dwarfism, compact rosettes, backwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…Consequently, the expression of ARF2 was repressed by these miRNAs and thus regulated pistil development. Moreover, TCP2 ( TEOSINTE BRANCHED/CYCLOIDEA/PCF ) transcription factor genes and MYB33, which belong to a GAMYB-like family of transcription factors, are also targets of miR319/miR319a/miR319e in our prediction, which agrees with previous reports [10,66]. Therefore, it is conceivable that the over-expression of miR319/miR319a/miR319e may contribute to an increase in imperfect flower ratios in pistil development.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the expression of ARF2 was repressed by these miRNAs and thus regulated pistil development. Moreover, TCP2 ( TEOSINTE BRANCHED/CYCLOIDEA/PCF ) transcription factor genes and MYB33, which belong to a GAMYB-like family of transcription factors, are also targets of miR319/miR319a/miR319e in our prediction, which agrees with previous reports [10,66]. Therefore, it is conceivable that the over-expression of miR319/miR319a/miR319e may contribute to an increase in imperfect flower ratios in pistil development.…”
Section: Discussionsupporting
confidence: 92%
“…Recent microarray analyses showed that many genes encoding proteins that accumulate during embryogenesis (e.g., AtLEA3-1-4) are remarkably upregulated in AtMYB118-overexpressed transgenic plants. These results suggest that AtMYB118 plays an important role during embryogenesis and seed maturation (Zhang et al 2009). …”
Section: Hormones and Regulation Of Atlea3 Groupmentioning
confidence: 95%
“…Dwarfism is an aberrant plant phenotype that could be induced by over-expression of MYB transcription factors (Zhang et al 2009), single virulence factor (Hoshi et al 2009), brassinosteroid receptor gene (Morinaka et al 2006), extremely hydrophobic peptides (Dresselhaus et al 2005), glutamate decarboxylase (Akama and Takaiwa 2007), fungal pectin methylesterase (Hasunuma et al 2004), regulator of gene expression (Mussig et al 2000), phytochrome A (Stockhaus et al 1992), and the Agrobacterium tumefaciens nopaline transferred DNA iaaH gene (Sitbon et al 1992). Dwarfism was also observed in transgenic rice plant expressing an antisense cDNA for the alpha subunit of rice heterotrimeric G protein (Fujisawa et al 1999).…”
Section: Introductionmentioning
confidence: 99%